Sources of variability in springwater chemistry in Fool Creek, a high‐elevation catchment of the Rocky Mountains, Colorado, USA. Issue 3 (15th March 2021) - Rhoades, Charles C.; Fegel, Timothy S.; Covino, Timothy P.; Dwire, Kathleen A.; Elder, Kelly
Abstract: Springs are the point of origin for most headwater streams and are important regulators of their chemical composition. We analysed solute concentrations of water emerging from 57 springs within the 3 km 2 Fool Creek catchment at the Fraser Experimental Forest and considered sources of spatial variation among them and their influence on the chemical composition of downstream water. On average, calcium and acid neutralizing capacity (bicarbonate‐ANC) comprised 50 and 90% of the cation and anion charge respectively, in both spring and stream water. Variation in inorganic chemical composition among springs reflected distinct groundwater sources and catchment geology. Springs emerging through glacial deposits in the upper portion of the catchment were the most dilute and similar to snowmelt, whereas lower elevation springs were more concentrated in cations and ANC. Water emerging from a handful of springs in a geologically faulted portion of the catchment were more concentrated than all others and had a predominant effect on downstream ion concentrations. Chemical similarity indicated that these springs were linked along surface and subsurface flowpaths. This survey shows that springwater chemistry is influenced at nested spatial scales including broad geologic conditions, elevational and spatial attributes and isolated local features. Our results highlight the role of overlapping factors on solute export from headwater catchments. Abstract : Emergent groundwater springs (dots) and associated wetlands (gray shading) in the Fool Creek catchment at the Fraser Experimental Forest, Colorado. The chemical composition of springwater reflected distinct groundwater sources and varied with elevation and among catchment zones. Acid neutralizing capacity (see Figure) and other inorganic constituents were more concentrated in springwater emerging from several springs in a geologically faulted portion of the catchment, and these had a predominant effect on downstream ion concentrations.